2018
DOI: 10.1159/000494573
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotic Drug Olanzapine Deregulates Hepatic Lipid Metabolism and Aortic Inflammation and Aggravates Atherosclerosis

Abstract: Background/Aims: Olanzapine, an atypical antipsychotic drug, has therapeutic effects for schizophrenia. However, clinical reports indicate that patients taking atypical antipsychotic drugs are at high risk of metabolic syndrome with unclear mechanisms. We investigated the effect of olanzapine on atherosclerosis and the mechanisms in apolipoprotein E-null (apoE-/-) mice. Methods: ApoE-/- mice were used as in vivo models. Western blot analysis was used to evaluate protein expression. Conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 46 publications
(71 reference statements)
2
17
1
1
Order By: Relevance
“…This reduced vascular inflammation may also include a component resulting from the observed decrease in total plasma and LDL cholesterol by drug treatment. Consistent with our proposed model, a recent study found that the antipsychotic drug olanzapine, a 5-HT 2A receptor inverse agonist, increases serum levels of total cholesterol, non-HDL, HDL-c, and triglycerides, deregulates hepatic lipid metabolism, and increases aortic proinflammatory protein expression (VCAM-1, TNF-α, and IL-6) in apoE −/− mice 59 . Along a similar vein, the 5-HT 2C selective agonist lorcaserin effectively reduces appetite to induce weight loss, a result we do not see with ( R )-DOI in our study.…”
Section: Discussionsupporting
confidence: 85%
“…This reduced vascular inflammation may also include a component resulting from the observed decrease in total plasma and LDL cholesterol by drug treatment. Consistent with our proposed model, a recent study found that the antipsychotic drug olanzapine, a 5-HT 2A receptor inverse agonist, increases serum levels of total cholesterol, non-HDL, HDL-c, and triglycerides, deregulates hepatic lipid metabolism, and increases aortic proinflammatory protein expression (VCAM-1, TNF-α, and IL-6) in apoE −/− mice 59 . Along a similar vein, the 5-HT 2C selective agonist lorcaserin effectively reduces appetite to induce weight loss, a result we do not see with ( R )-DOI in our study.…”
Section: Discussionsupporting
confidence: 85%
“…[56][57][58] ApoE deficiency has effects on both FAO and FAS. 59 The contribution of ApoE to the immune balance of Th17/Treg in our study needs more in-depth investigations.…”
Section: Discussionmentioning
confidence: 81%
“…Treg cells rely mainly on fatty acid oxidation, whereas Th17 cells demonstrate a reliance upon fatty acid synthesis 56‐58 . ApoE deficiency has effects on both FAO and FAS 59 . The contribution of ApoE to the immune balance of Th17/Treg in our study needs more in‐depth investigations.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, atypical antipsychotics can also provoke dyslipemia or hyperlipidemia, however, the mechanisms by which this occurs are not clearly known ( Jeon and Kim, 2017 ). It is proposed that olanzapine alters hepatic lipid metabolism by interfering with lipogenesis, lipoprotein internalization and cholesterol clearance, favoring the accumulation of lipids and the development of hyperlipidemia ( Chen et al, 2018 ).…”
Section: Metabolic Effects Of Risperidone Olanzapine and Aripiprazolementioning
confidence: 99%